HTK‐N as a new preservation solution for human kidney preservation: Results of a pilot randomized controlled clinical phase II trial in living donor transplantation. Issue 3 (8th December 2021) - Hoyer, Dieter P.; Benkö, Tamas; Gallinat, Anja; Lefering, Rolf; Kaths, Moritz; Kribben, Andreas; Korth, Johannes; Rauen, Ursula; Treckmann, Juergen W.; Paul, Andreas
Abstract: Background: HTK‐N was developed based on the traditional HTK preservation solution, resulting in stronger protection against reactive oxygen species as well as better tolerance to hypothermia and ischemia. Aim of the present study was to compare HTK‐N to HTK in clinical kidney transplantation demonstrating safety and non‐inferiority. Methods: We performed a randomized controlled single blinded clinical phase II trial in patients undergoing living donor kidney transplantation. After retroperitoneoscopic nephrectomy kidneys were either perfused and stored with classical HTK solution or the new HTK‐N solution. Primary endpoint was the glomerular filtration rate (eGFR according to CKD EPI) 3 months after transplantation. Secondary endpoints included graft and patient survival beside others. Results: The study included 42 patients, of which 22 were randomized in the HTK‐N group and 20 in the HTK group. The primary end point showed a mean eGFR of 55.4 ± 14.0 ml/min/1.73 m 2 in the HTK group compared to a GFR of 57.2 ± 16.7 ml/min/m 2 in the HTK‐N group ( P = .72). Regarding secondary endpoints, there were no apparent differences. Posttransplant graft and patient survival was 100%. Conclusion: This study is the first clinical application of HTK‐N for kidney preservation and demonstrates non‐inferiority compared to HTK in the setting of living donor kidney transplantation.